1969
DOI: 10.1177/070674376901400408
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy in Aged Psychiatric Patients

Abstract: The psychopathology of organic brain syndromes and functional psychiatric disorders in the aged has been outlined, and the various specific and non-specific physical therapies for psychiatric disorders occurring in this age group have been discussed. The indications for electroconvulsive therapy are restricted to depressions, particularly first and acute depressions in this population. Various drug therapies are successfully employed in numerous geriatric conditions. Pharmacotherapy is discussed under six hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Only a few evaluated anxiety in subjects over age 60; their results were inconclusive about whether there is increased prevalence of anxiety with advancing age. Kral and Papetropoulus (1965) noted that only a small number of elderly patients can be appropriately diagnosed as having phobic anxiety reactions; Lehmann and Ban (1969) suggest that intrapsychic conflicts are rarely central to the anxiety seen in the elderly. Raskin (1979) too has suggested that anxiety in the elderly generally does not take the same form as anxiety in younger persons; in older adults it is often associated with some physical disorder.…”
Section: Affective Status and Psychopathologymentioning
confidence: 99%
“…Only a few evaluated anxiety in subjects over age 60; their results were inconclusive about whether there is increased prevalence of anxiety with advancing age. Kral and Papetropoulus (1965) noted that only a small number of elderly patients can be appropriately diagnosed as having phobic anxiety reactions; Lehmann and Ban (1969) suggest that intrapsychic conflicts are rarely central to the anxiety seen in the elderly. Raskin (1979) too has suggested that anxiety in the elderly generally does not take the same form as anxiety in younger persons; in older adults it is often associated with some physical disorder.…”
Section: Affective Status and Psychopathologymentioning
confidence: 99%